Jeremy Bentham’s Utilitarianism Theory Methodology in the Corporation Law System In Indonesia - Boy Aditya Prakasa; Elisatris Gultom (Badan Penerbit STIEPARI Press, 2025)
This study examines the relevance and application of Jeremy Bentham's theory of utilitarianism in the context of corporate law in Indonesia. The theory of utilitarianism, based on the principle of